1994
DOI: 10.1007/bf00190734
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline infusion induces activation of the lymphocyte Na+/H+ antiport and cytosolic alkalinization in healthy human subjects

Abstract: The Na+/H+ antiport is a membrane transport protein that extrudes intracellular protons in exchange for extracellular sodium. Some details of its physiological and pathophysiological role remain poorly defined. Experimental evidence suggests that the antiporter is involved in the regulation of cell volume. In the present study, we therefore investigated the activity of the lymphocyte Na+/H+ antiport in nine healthy volunteers following acute hypertonic (2.5%) saline infusion (4 mmol NaCl/kg over 120 min). Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We have previously shown that acute infusion of hypertonic (2 . 5%) saline with a marked rise in extracellular osmolality is also associated with an activation of the lymphocyte Na þ /H þ antiport [34]. As in vitro and ex vivo studies have clearly established a role for NHE in the regulation of cell volume [35], this study suggests that changes in extracellular osmolality with consecutive changes in cell volume may also participate in the regulation of the Na þ /H þ antiport in vivo.…”
Section: Discussionmentioning
confidence: 53%
“…We have previously shown that acute infusion of hypertonic (2 . 5%) saline with a marked rise in extracellular osmolality is also associated with an activation of the lymphocyte Na þ /H þ antiport [34]. As in vitro and ex vivo studies have clearly established a role for NHE in the regulation of cell volume [35], this study suggests that changes in extracellular osmolality with consecutive changes in cell volume may also participate in the regulation of the Na þ /H þ antiport in vivo.…”
Section: Discussionmentioning
confidence: 53%
“…But still other possible mechanisms may be involved, as previously mentioned (25). Enforced activity of cellular Na ϩ /H ϩ exchangers (18,36) as well as Na ϩ /H ϩ ion exchanges on the extracellular glycosaminoglycans (19) and/or a Na-induced expansion of extracellular volume, resulting in a decrease in HCO 3 Ϫ reabsorption (3,38,52,58), can contribute to mediation of the effect of NaCl on acid-base balance. Summarizing, with high NaCl intake, renal loss of bicarbonate but also excess acid production could be reasonably expected to affect acid-base status.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the reason for the decreased pH and bicarbonate concentration could not be an addition of metabolic acids by ingestion or infusion of acids, because the subjects' intake of acid‐inducing foods was not higher during high salt intake. Studies from Dusing et al ( (59)) and Kessler et al ( (60)) have shown significant stimulation of the Na + /H + exchanger during acute saline (0.9%) infusion accompanied by cytosolic alkalinization and extracellular acidification and accomplished by decreases in pH, bicarbonate, and base excess.…”
Section: Discussionmentioning
confidence: 99%